2022
DOI: 10.1038/s41467-022-30390-9
|View full text |Cite
|
Sign up to set email alerts
|

Codon-specific Ramachandran plots show amino acid backbone conformation depends on identity of the translated codon

Abstract: Synonymous codons translate into chemically identical amino acids. Once considered inconsequential to the formation of the protein product, there is evidence to suggest that codon usage affects co-translational protein folding and the final structure of the expressed protein. Here we develop a method for computing and comparing codon-specific Ramachandran plots and demonstrate that the backbone dihedral angle distributions of some synonymous codons are distinguishable with statistical significance for some sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(95 citation statements)
references
References 56 publications
6
86
3
Order By: Relevance
“…True codon information did not improve prediction of φ or ψ in a statistically significant manner for the α mode. This result is expected, since the α mode is more rigid in structure than the β mode and so less likely to accommodate small, local structural variability 25,26 , and agrees with the findings in our previous work showing that many synonymous codon backbone dihedral angle distributions are statistically significantly different in the β mode, but no statistically significant differences in distributions for the α mode 8 . Table 1 also shows that the φ mean absolute error (MAE) is lower than for ψ and that the error improvement using true codons is greater for φ , in both β and α modes.…”
Section: Hypothesis 1 (Codon-structure): Synonymous Codon Sequence In...supporting
confidence: 92%
See 1 more Smart Citation
“…True codon information did not improve prediction of φ or ψ in a statistically significant manner for the α mode. This result is expected, since the α mode is more rigid in structure than the β mode and so less likely to accommodate small, local structural variability 25,26 , and agrees with the findings in our previous work showing that many synonymous codon backbone dihedral angle distributions are statistically significantly different in the β mode, but no statistically significant differences in distributions for the α mode 8 . Table 1 also shows that the φ mean absolute error (MAE) is lower than for ψ and that the error improvement using true codons is greater for φ , in both β and α modes.…”
Section: Hypothesis 1 (Codon-structure): Synonymous Codon Sequence In...supporting
confidence: 92%
“…We have recently uncovered a direct association between codon identity and the backbone, φ and ψ, dihedral angles of the amino acid it encodes, by comparing dihedral angle distributions of synonymous codons 8 . To determine if this association is detectable using other approaches, we apply regression and classification models based on machine learning and deep neural networks (DNNs) to determine: (i) whether protein structure prediction may be improved by using the genetic, rather than amino acid, sequence; (ii) whether the codon from which an amino acid was translated may be predicted given the final protein structure.…”
Section: Introductionmentioning
confidence: 99%
“…Since its definition, which dates back to nearly sixty years ago [ 22 ], the Ramachandran plot in its many declinations has inspired a remarkable number of insightful studies that have had a tremendous impact on structural biology [ 23 , 24 , 25 , 26 ]. Remarkable examples can also be found in the recent literature [ 45 , 46 , 47 , 48 ]. We here exploited this tool by initially identifying regions of the plot for which amino acid residues have similar conformational propensities.…”
Section: Discussionmentioning
confidence: 89%
“…It has been proposed that some proteins may fold into native structures that are more kinetically accessible than conformations of the lowest free energy [ 99 ]. Indeed, experimental observations have been reported that synonymous codon substitutions result in conformational changes in the translated proteins, due to kinetic changes in the co-translational folding of the nascent chain on the ribosome [ 100 , 101 , 102 , 103 ]. These results are consistent with the idea that the native structures of some proteins may be determined by kinetics rather than thermodynamics.…”
Section: Discussionmentioning
confidence: 99%